PEMERINTAHAN PRESIDENSIEL DAN TUGAS KONSTITUSINALNYA UNTUK MENSEJAHTERAKAN RAKYAT - Tamudin, M (Nurani, 2013)
Abstract:  As the holder of a general power of government authorities must hold administrative power. The President as head of government is the highest authority of the administration of the state. The scope of the administrative organization of the country includes a very spacious room that is all that has to do with the authority of the state administration.ملخص: كما صاحب سلطة عامة من سلطات الحكومة يجب أن يحمل السلطة الإدارية. الرئيس ورئيس الحكومة هو أعلى سلطة في إدارة شؤون الدولة. ويشمل نطاق التنظيم الإداري للدولة وغرفة فسيحة جدا وهذا هو كل ما له علاقة مع السلطة من الجهاز الإداري للدولة.Kata kunci: negara, pemerintah, warga negara dan kesejahteraan